Hybrid MXene (Ti3C2Tx)/polyaniline nanosheets as additives for enhancing anticorrosion properties of Zn-epoxy coating - Kaewsaneha C. (2023)
Corrosion is a problematic and costly issue in various technological fields, especially in marine, automobile, rail, and building industries. To effectively cope with this issue, transition-metal carbides (Ti3C2Tx), a 2-dimensional conductive material, functionalized with polyaniline (PANI) have been developed and applied as anticorrosion additive in a Zn-epoxy coating, due to its high specific surface area, excellent electronic conductivity and ease of surface modifications. Ti3C2Tx functionalized with PANI (Ti3C2Tx/PANI) was fabricated via an in-situ polymerization of aniline monomer using ammonium persulphate initiator. The presence of crystalline PANI molecules in the interlayer and on the surface of Ti3C2Tx was reflected by X-ray diffraction (XRD), scanning electron microscopy with energy dispersive X-ray spectrometer (SEM-EDX), transmission electron microscopy (TEM), Fourier-transform infrared (FTIR) spectroscopy, and thermogravimetric analysis (TGA). The formation of crystalline PANI in the interlayer of Ti3C2Tx created the conductive pathway for increased electrical conductivity and enhanced compatibility with the epoxy matrix. The Ti3C2Tx/PANI composites were sonicated into ultrathin nanosheets, dispersed in the Zn-epoxy resin, and applied as an anticorrosion coating on steel substrates. Their anticorrosion performance was evaluated using an accelerated immersion test in severe acidic solution. The inclusion of 2.0 wt% Ti3C2Tx/PANI into the Zn-epoxy coating showed lower amounts of corrosion products, water adsorption, and leached iron concentration than pure epoxy and the Zn-epoxy coatings, indicating an enhanced anticorrosion property of the developed composites.